Impact evaluation of Swiss Medical Board reports on routine care in Switzerland: a case study of PSA screening and treatment for rupture of anterior cruciate ligament (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: Evidence-based recommendations play an important role in medical decision-making, but barriers to adherence are common. In Switzerland, the Swiss Medical Board (SMB) publishes evidence reports that conclude with recommendations. We assessed the impact of two SMB reports on service provision (2009: Recommendation of conservative treatment as first option for rupture of the anterior cruciate ligament of the knee; 2011: Recommendation against PSA screening for prostate cancer). METHODS: We performed an observational study and assessed quantitative data over time via interrupted times series analyses. The primary outcome was the quarterly number of performed prostate-specific antigen (PSA) tests and the annual rates of surgical ACL repair in patients with ACL rupture. Data were adjusted for time trends and relevant confounders. RESULTS: We analysed PSA tests in 662,874 outpatients from 2005–2013 and treatment data in 101,737 patients with knee injury from 1990–2011. For the number of PSA tests, the secular trend before the intervention showed a continuous but diminishing increase over time. A statistically significant reduction in tests was estimated immediately after the intervention, but a later return to the trend before the intervention cannot be ruled out. The rate of surgical ACL repair had already declined after the late 1990s to about 55% in 2009. No relevant additional change emerged in this secular trend after the intervention. CONCLUSIONS: Despite some evidence of a possible change, we did not find a sustained and significant impact of SMB recommendations in our case study. Further monitoring is needed to confirm or refute these findings.